2020
DOI: 10.11606/1807-0205/2020.60.18
|View full text |Cite
|
Sign up to set email alerts
|

First records of ectoparasitic insects (Diptera: Hippoboscoidea) of bats in the department of Caldas, Colombia

Abstract: In Colombia, the taxonomical understanding of ectoparasites (Diptera: Streblidae and Nycteribiidae) of bats is scarce, despite the high diversity of hosts. This fact reflects the lack of important information on the group and poses the need for studies that expand the knowledge on bat ectoparasites in different regions of the country. The aim of this study was to contribute pioneer knowledge on bat ectoparasitic insects in the department of Caldas, located in the Central Andes Mountain range of Colombia. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…Basilia ferrisi is in the speiseri species group because females have two abdominal tergites and the second one has a slightly rounded posterior margin (Graciolli, 2010). This species is distributed in Brazil, Costa Rica, Colombia, Guyana, Panama, Peru, and Venezuela (Graciolli et al, 2007(Graciolli et al, , 2016Raigosa Álvarez et al, 2020) and the herein presented record, extend its geographic distribution to the Sucre department. Basilia ferrisi has been registered in a wide host diversity from the Phyllostomidae, Vespertilionidae, and Molossidae families (Graciolli et al, 2007), and here we add the vespertilionid bat Eptesicus brasiliensis.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Basilia ferrisi is in the speiseri species group because females have two abdominal tergites and the second one has a slightly rounded posterior margin (Graciolli, 2010). This species is distributed in Brazil, Costa Rica, Colombia, Guyana, Panama, Peru, and Venezuela (Graciolli et al, 2007(Graciolli et al, , 2016Raigosa Álvarez et al, 2020) and the herein presented record, extend its geographic distribution to the Sucre department. Basilia ferrisi has been registered in a wide host diversity from the Phyllostomidae, Vespertilionidae, and Molossidae families (Graciolli et al, 2007), and here we add the vespertilionid bat Eptesicus brasiliensis.…”
Section: Resultsmentioning
confidence: 57%
“…The genus Basilia has 53 species (Graciolli et al, 2007;Graciolli & Dick, 2009), and there are eight species registered from Colombia: Basilia anceps Guimarães & d'Andretta, 1956 (Caquetá); B. astochia Peterson & Maa, 1970 (Santander); B. bequaerti Guimarães & d'Andretta, 1956 (Tolima); B. constricta Guimarães & d'Andretta, 1956 (Bolívar); B. dubia Guimarães & d'Andretta, 1956 (Putumayo);B. ferrisi Schuurmans Stekhoven, 1931 (Antioquia, Bolívar, Caldas, Chocó, Meta, Santander); B. ferrisi Theodor & Peterson, 1964 (Córdoba); and B. wenzeli Guimarães & d'Andretta, 1956 (Cundinamarca) (Graciolli et al, 2016;Pastrana-Montiel et al, 2019;Raigosa Álvarez et al, 2020). Local inventories of bats along the country and the careful harvesting of their associated parasites (i.e., Tarquino-Carbonell et al, 2015;Raigosa Álvarez et al, 2020) have allowed to discover a high diversity of bat flies and even new associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Neotropical countries with a high number of bat species such as Colombia (~ 217 species) and Venezuela (172 species) ( Delgado-Jaramillo et al 2016 ; Ramírez-Chaves et al 2021 ), studies on Streblidae and Nycteribiidae are few and discontinuous (e.g., Tamsitt and Fox 1970 ; Marinkelle and Grose 1981 ; Guerrero 1994 ). In recent years, new research has expanded the knowledge about these ectoparasites in both countries ( Herrera-Sepúlveda 2013 ; Tarquino-Carbonell 2014 ; Tarquino-Carbonell et al 2015 ; Dick et al 2016 ; Durán et al 2018 ; Calonge-Camargo and Pérez-Torres 2018 ; Guerrero 2019 ; Liévano-Romero et al 2019 ; Raigosa Álvarez et al 2020 ; Cañizales and Guerrero 2022 ). Nonetheless, there are very few studies in the Orinoquia Region, a hydrographic basin that converges into the Orinoco River, covering an area of almost 989,000 km 2 ( Domínguez 1998 ), and shared by both countries ( Guimarães 1972 ; Wenzel 1976 ; Dick et al 2016 ; Liévano-Romero et al 2019 ; López Rivera et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 125 Streblidae species reported in Colombia and Venezuela (81 and 107 respectively; Wenzel 1976 ; Tarquino-Carbonell et al 2015 ; Dick et al 2016 ; Duran et al 2017; Calonge-Camargo and Pérez-Torres 2018 ; Guerrero 2019 ; Liévano-Romero et al 2019 ; Ascuntar-Osnas et al 2020 ; Raigosa Álvarez et al 2020 ; López Rivera et al 2022 ), 124 have been documented for the Orinoquia in ~ 96 bat species of the families Emballonuridae , Molossidae , Mormoopidae , Natalidae , Noctilionidae , Phyllostomidae , and Vespertilionidae ( Wenzel 1976 ; Dick et al 2016 ; Guerrero 2019 ; Liévano-Romero et al 2019 ; López Rivera et al 2022 ). Similarly, of the 16 Nycteribiidae reported in Colombia and Venezuela (11 and 13, respectively; Wenzel and Tipton 1966 ; Graciolli et al 2016 ; Pastrana-Montiel et al 2019 ; Raigosa Álvarez et al 2020 ; López Rivera et al 2022 ), 12 have been found in the Orinoquia (two in Colombia, 12 in Venezuela; Wenzel and Tipton 1966 ; Graciolli et al 2016 ; López Rivera et al 2022 ). Besides the high number of bats and bat flies documented in the Orinoquia, the interaction structure that might be evaluated using ecological or interaction networks ( Dormann et al 2009 ), has not been addressed.…”
Section: Introductionmentioning
confidence: 99%